2016
DOI: 10.1016/j.cmet.2015.10.003
|View full text |Cite|
|
Sign up to set email alerts
|

Thermoneutral Housing Accelerates Metabolic Inflammation to Potentiate Atherosclerosis but Not Insulin Resistance

Abstract: SUMMARY Chronic, low-grade inflammation triggered by excess intake of dietary lipids has been proposed to contribute to the pathogenesis of metabolic disorders, such as obesity, insulin resistance, type 2 diabetes, and atherosclerosis. Although considerable evidence supports a causal association between inflammation and metabolic diseases, most tests of this link have been performed in cold-stressed mice that are housed below their thermoneutral zone. We report here that thermoneutral housing of mice has a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 68 publications
12
104
0
Order By: Relevance
“…Tnfa expression did not increase in mice at 4 or 10 weeks of a HFD (Supplemental Figure 5D). These findings are consistent with previous reports showing that mice develop adipose and systemic insulin resistance within several days to 4 weeks of a HFD (44,45), whereas the number of M1 macrophages in WAT increases only within 8 to 10 weeks of a HFD (10,15,45,46). The finding that HFD-induced insulin resistance precedes the accumulation of M1 macrophages is consistent with our above conclusion that insulin resistance leads to inflammation.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Tnfa expression did not increase in mice at 4 or 10 weeks of a HFD (Supplemental Figure 5D). These findings are consistent with previous reports showing that mice develop adipose and systemic insulin resistance within several days to 4 weeks of a HFD (44,45), whereas the number of M1 macrophages in WAT increases only within 8 to 10 weeks of a HFD (10,15,45,46). The finding that HFD-induced insulin resistance precedes the accumulation of M1 macrophages is consistent with our above conclusion that insulin resistance leads to inflammation.…”
Section: Resultssupporting
confidence: 83%
“…However, it has been demonstrated that immunocompromised mice are not protected from systemic insulin resistance induced by a short-term high-fat diet (HFD) (14). Furthermore, Tian et al have shown that adipose tissue inflammation is dispensable for local and systemic insulin resistance (15). Another study has shown that inhibition of adipose tissue inflammation results in glucose intolerance, suggesting that inflammation may even be a mechanism to counter insulin resistance (16).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our findings and those of others 53 , Tian et al reported improved glucose clearance in mice housed at 30°C. However, they also reported worsened atherosclerosis along with modestly elevated cholesterol, albeit with minimal disease effects at the aortic arch and the most dramatic effects in the descending aorta 22 . Aortic sinus disease, which we quantified in the present study along with aortic disease at multiple time points, was not examined by Tian et al Giles et al failed to find a major shift in plasma cholesterol but nonetheless reported that enhanced atherosclerosis was worsened in Apoe −/− mice fed a high fat diet, but there was no disease change in Apoe −/− mice fed a chow diet.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, some reports indicate that cold temperature, a powerful stimulus for brown and beige fat and UCP1 activation, enhances atherosclerosis 21 . However, other studies suggest that thermoneutral housing at the warm temperature of 30°C—the temperature at which energy expenditure is not needed to maintain body temperature—enhances atherosclerosis 22 . The impact of housing temperature on blood monocyte counts has scarcely been discussed, despite reported connections of sympathetic activation to both beige fat activation and monocytosis, as discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…116 An emerging consideration is the temperature of the vivarium, which has been demonstrated to alter the development of mouse atherosclerosis. 171,172 Mice are usually housed in rooms that are ~20°C, whereas their thermoneutrality is ~30°C. Although maintaining mice under thermoneutral conditions is not usually practical, these recent publications highlight the need to monitor room temperatures throughout the course of the study.…”
Section: Vivarium Conditionsmentioning
confidence: 99%